Lycium barbarum polysaccharide inhibits ischemia-induced autophagy by promoting the biogenesis of neural stem cells-derived extracellular vesicles to enhance the delivery of miR-133a-3p - Rong Li; Wenjie Duan; Tingle Feng; Chenyang Gu; Qiankun Zhang; Jun Long; Shiying Huang; Lukui Chen (BMC, 2023)
Abstract Background Neural stem cell-derived extracellular vesicles (NSC-EVs) mediated endogenous neurogenesis determines a crucial impact on spontaneous recovery after stroke. Here, we checked the influence of Lycium barbarum polysaccharide (LBP) on the biogenesis of NSC-EVs and then focused on studying mechanisms of LBP in ameliorating ischemic stroke outcome. Methods LBP was prepared to precondition NSCs and isolate EVs. MCAO models and primary NSCs were administrated to evaluate the therapeutic effect. RT-PCR, western blot, flow cytometry, and immunofluorescence techniques were performed to explore the mechanism. Results LBP pretreatment increased the production of NSC-EVs and improved the neuroprotective and recovery effects of NSC-EV in ischemic stroke mice. LBP-pretreated NSC-EV in a dose-dependent manner substantially reduced neuronal death compared with NSC-EV. Screening of the signaling cascade involved in the interaction between NSC-EV and neurons revealed that AMPK/mTOR signaling pathway inhibited autophagic activity in neurons receiving either treatment paradigm. NSC-EVs but not EVs collected from NSCs pretreated with the anti-miR-133a-3p oligonucleotide reduced cell death, whereas the anti-oligonucleotide promoted autophagy activity and cell death by modulating AMPK/mTOR signaling in OGD-induced primary neurons. Conclusion LBP activated AMPK/mTOR signaling pathway by increasing the enrichment and transfer of miR-133a-3p in NSC-EVs to inhibit stroke-induced autophagy activity.